The Effect of Gratitude on Parental Stress among Mothers’ of Early Children - Ika Febrian Kristiana; Darosy Endah Hyoschamina; Niken Fatimah (Intelektual Pustaka Media Utama, 2018)
The stress of parenting as a distress experience in carrying out the demands of parenting role becomes greater experienced by the mother as the primary caregiver as a culture in Indonesia. Be grateful to be a strength-based intervention aimed at strengthening positive emotions and protecting individuals from psychological problems. This experimental study aims to test the effectiveness of gratitude in reducing maternal stress. The experimental design between subjects was selected by dividing the 70 mothers who had early childhood into two groups: the experimental and control group. The data analysis using 2 independent samples test with R statistic showed (p = .023; Cohen's d = .183), and Wilcoxon 2 related samples test (p = .0087) showed that gratitude training was effective to decrease maternal stress. Being grateful for a moral response based on personal reinforcement through thoughts, emotions, and positive and pleasant attitudes that then lead to the ability to give goodness to others. The findings of this study become interesting when examined also from the social context such as the existence of social support where the attitude of gratitude is related to it.